Psychological factors of aggressive behaviour in patients of forensic psychiatry wards with the diagnosis of schizophrenia. (September 2020) - Markiewicz, Inga; Pilszyk, Anna; Kudlak, Grzegorz
Abstract: Scientific research shows that the likelihood of aggressive behaviour in people with mental disorders compared to healthy people is usually higher than among healthy people. Considering the social harmfulness of acts committed by persons suffering from schizophrenia, a thorough analysis of their conditions is recommended. The paper presents the results of research conducted by a team from the Forensic Psychiatry Clinic of the Institute of Psychiatry and Neurology (IPiN) in Warsaw regarding the psychological determinants of aggressive behaviour of people diagnosed with schizophrenia. The analysis covers selected demographic variables, personality traits as well as the level and type of aggression presented, including previously undertaken violent behaviour. This article includes the results of studies on patients diagnosed with schizophrenia, interned in the Forensic Psychiatry Clinic of IPiN, as well as patients with schizophrenia (addicted and non-addicted) staying in general psychiatric wards.